PCR-RDB assay for detection of vibrio cholerae - Yun, Foong Sui (Universiti Sains Malaysia, 2005)
A colorimetric detection method has been designed and optimized by immobilizing a specific DNA probe onto Biodyne C membrane and hybridize it with heat denatured biotin labeled PCR amplicon to detect the presence of the hemM gene of Vibrio cholerae. Therefore it can be used to replaced agarose gel electrophoresis and conventional culture method which are very low in sensitivity for diagnosis of cholera. This method was refered to as PCR-RDB assay. Optimization of the PCR-Rerverse Dot Blot assay include hybridization temperature, amount of PCR amplicon, timing of the assay, optimizing of biotin incorporation in PCR amplicon, dilution of streptavidin-alkaline phosphatase conjugate used and development of a control positive for the assay. PCR-RDB assay can be used in detection of biological or environmental samples to help in control of cholera cases in high incidence area.